2023
DOI: 10.3390/antibiotics12091388
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic/Pharmacodynamic Target Attainment of Continuous Infusion Piperacillin–Tazobactam or Meropenem and Microbiological Outcome among Urologic Patients with Documented Gram-Negative Infections

Pasquale Maria Berrino,
Milo Gatti,
Matteo Rinaldi
et al.

Abstract: (1) Objectives: To describe the relationship between pharmacokinetic/pharmacodynamic (PK/PD) target attainment of continuous infusion (CI) piperacillin–tazobactam or meropenem monotherapy and microbiological outcome in a case series of urological patients with documented Gram-negative infections. (2) Methods: Patients admitted to the urology ward who were treated with CI piperacillin–tazobactam or meropenem monotherapy for documented Gram-negative infections and underwent real-time therapeutic drug monitoring … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…The PD determinant selected for assessing the efficacy of piperacillin–tazobactam monotherapy was a joint PK/PD target, as previously described [ 38 ]. Briefly, the joint PK/PD target was considered optimal whenever the piperacillin f C ss /MIC ratio was >4 and the tazobactam f C ss /target concentration (C T ) ratio was >1 (where C T is the fixed tazobactam target concentration of 4 mg/L proposed by the EUCAST for testing the in vitro susceptibility of the piperacillin–tazobactam combination); it was considered quasi-optimal whenever only one of the two thresholds was attained and suboptimal whenever none of the two was attained [ 38 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The PD determinant selected for assessing the efficacy of piperacillin–tazobactam monotherapy was a joint PK/PD target, as previously described [ 38 ]. Briefly, the joint PK/PD target was considered optimal whenever the piperacillin f C ss /MIC ratio was >4 and the tazobactam f C ss /target concentration (C T ) ratio was >1 (where C T is the fixed tazobactam target concentration of 4 mg/L proposed by the EUCAST for testing the in vitro susceptibility of the piperacillin–tazobactam combination); it was considered quasi-optimal whenever only one of the two thresholds was attained and suboptimal whenever none of the two was attained [ 38 ].…”
Section: Methodsmentioning
confidence: 99%
“…Some studies showed that when using beta-lactam/beta-lactamase inhibitor combinations (BL/BLIc), attaining optimal joint pharmacokinetic/pharmacodynamic (PK/PD) targets of both the BL and the BLI may be beneficial in terms of both maximizing the clinical/microbiological outcome and preventing resistance development [ 38 , 39 ]. In this scenario, implementing a real-time therapeutic drug monitoring (TDM)-based expert clinical pharmacological advice (ECPA) program may represent a valuable approach for assessing the optimal joint PK/PD target attainment of BL/BLIc administered by continuous infusion (CI) [ 40 ].…”
Section: Introductionmentioning
confidence: 99%
“…The so-called joint PK/PD target was selected as best PD determinant of piperacillintazobactam efficacy. Specifically, the joint PK/PD target was defined as optimal when both the piperacillin f C ss /MIC ratio was >4 and the tazobactam f C ss /C T ratio was >1 (where C T corresponded to the fixed tazobactam target concentration used by the EUCAST for the in vitro standard susceptibility testing, namely, 4 mg/L), and quasi-optimal or suboptimal when only one or none of the two thresholds were attained, respectively [27]. Attainment of this aggressive PK/PD target with beta-lactams was previously associated with both maximal clinical efficacy and suppression of resistance emergence among Gram-negative pathogens [13][14][15][16][17][18][19].…”
Section: Definition Of Optimized Joint Pk/pd Target Attainment Of Pip...mentioning
confidence: 99%
“…All studies assessing aggressive PK/PD target attainment of piperacillin-tazobactam were based solely on piperacillin concentrations, without taking tazobactam exposure into account. Indeed, with regard to beta lactam (BL)-beta lactamase inhibitor (BLI) combinations, including piperacillin-tazobactam, the innovative concept of the so-called joint PK/PD target was recently proposed [27,28], in which optimal PK/PD target attainment should be achieved for both the BL and for the combined BLI simultaneously [27]. Additionally, it should not be overlooked that selecting the most appropriate dosing regimen may be extremely challenging in critically ill patients, considering that piperacillin-tazobactam pharmacokinetics may be significantly affected by sepsis-related pathophysiological changes [29][30][31][32].…”
Section: Introductionmentioning
confidence: 99%
“…With regard to meropenem, PK/PD target attainment was defined as being optimal when the f C ss /MIC ratio was >4 (equivalent to 100%f T > 4 × MIC ), and quasi-optimal or suboptimal when the f C ss /MIC ratio was 1-4 or <1 (equivalent to 100%f T 1-4 × MIC and to <100%f T 1 × MIC ), respectively, as previously reported [58]. With regard to the BL/BLI combinations, namely piperacillin-tazobactam, ceftazidime-avibactam, and meropenem-vaborbactam, a joint PK/PD target was considered [59,60]. With regard to piperacillin-tazobactam, the joint PK/PD target was defined as being optimal if both the piperacillin f C ss /MIC ratio was >4 and the tazobactam f C ss /target concentration (C T ) ratio was >1, and quasi-optimal or suboptimal if only one or none of the two thresholds was attained, respectively [59].…”
Section: Data Collectionmentioning
confidence: 99%